Rekomendasi Perbaikan User Interface dan Evaluasi Tingkat Kebergunaan Pada Aplikasi Angso Duo Online Menggunakan Usability Testing - Ibnu Sani Wijaya; Xaverius Sika; Elvi Yanit; Ali Sadikin (JURIKOM (Jurnal Riset Komputer), 2022)
The Angso Duo Online (ADO) application is an alternative for the people of Jambi City to shop easily, safely and quickly online. In a pandemic condition until now, this application has played a role in serving the people of the city of Jambi in facilitating access to shopping at the Angso Duo Jambi market using this ADO application. this application in terms of serving the people of the city of Jambi shopping online. The method used in this research is Usability Testing with the Smart PLS 3.0 software tool, and the number of respondents in this study is 128 respondents. The purpose of this study is to analyze and conduct testing in order to find problems that will be used as recommendations for improvement for developers to improve the Angso Duo online application for the better. The results of this study show that out of 5 hypotheses, only one hypothesis is accepted, namely H1 which means variable efficiency. the use of the angso duo online application can be accepted by the community. In the success rated time based efficiency test, the results were 92.85% and 0.00357/second, which means that the ADO application can be used by the people of the city of Jambi